2014
DOI: 10.1002/cncr.28599
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis and clinical correlation of metastatic colorectal cancer

Abstract: BACKGROUND Early identification of mutations may guide patients with metastatic colorectal cancer toward targeted therapies that may be life prolonging. The authors assessed tumor genotype correlations with clinical characteristics to determine whether mutational profiling can account for clinical similarities, differences, and outcomes. METHODS Under Institutional Review Board approval, 222 patients with metastatic colon adenocarcinoma (n = 158) and rectal adenocarcinoma (n = 64) who underwent clinical tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 28 publications
8
62
2
Order By: Relevance
“…To a certain extent, this observation may be driven by anatomy as the majority of colorectal cancers drain to the portal vein, thus promoting hematogenous spread to the liver [13]. Supporting this concept, the frequency of pulmonary metastases was increased in patients of our cohort with rectal cancer.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…To a certain extent, this observation may be driven by anatomy as the majority of colorectal cancers drain to the portal vein, thus promoting hematogenous spread to the liver [13]. Supporting this concept, the frequency of pulmonary metastases was increased in patients of our cohort with rectal cancer.…”
Section: Discussionsupporting
confidence: 64%
“…Further factors are likely to contribute to the site-specific appearance of metastases [13]. For example, certain alterations of the tumor cells appear to be associated with metastases to the lungs and lymph nodes [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Tran et al [8] reported a higher rate of peritoneal and distant lymph node metastases and a lower rate of lung metastases in BRAF mutated tumors. Similarly, Russo et al [19] reported a higher likelihood of BRAF mutations in patients with distant lymph node metastases at the site of first recurrence. Finally, Kawazoe et al [12] retrospectively studied the clinical-pathological features of BRAF mutations in Japanese patients with metastatic CRC and found that peritoneal metastases are more frequently observed in BRAF mutated patients.…”
Section: Ras and Braf Status Primary Tumor Location And Pattern Of Mmentioning
confidence: 85%
“…Several studies have reported an increased likelihood of peritoneal dissemination in BRAF mutant mCRC patients [8,9,19] . Yaeger et al [9] reported that patients with BRAF mutations were more likely to present with peritoneal metastases at initial diagnosis and less likely to have liver-limited metastases.…”
Section: Ras and Braf Status Primary Tumor Location And Pattern Of Mmentioning
confidence: 99%
“…From the clinical point of view, screening for RAS mutations is important in patients with colorectal carcinoma where the presence of K-RAS mutation is associated with poor response to anti-EGFR therapies [26][27][28]. However, in differentiated thyroid cancer, the detection of RAS mutation has not thus far determined any treatment decision.…”
Section: Discussionmentioning
confidence: 99%